SAT0422 URATE VOLUME AND DISTRIBUTION BY DUAL ENERGY CT: CLINICAL AND RADIOLOGICAL CORRELATION IN GOUT PATIENTS. (June 2019) - Gong, Bo; Warwas, Mark; O'keeffe, Michael; Tsao, Nicole; Vera, Mary De; Shojania, Kamran; Khosa, Faisal; Nicolaou, Savvas
Abstract : Background: Dual-energy CT (DECT) has shown tremendous potential as a novel non-invasive method of urate detection in patients with gout. Objectives: Our aim was to determine the concordance between urate volume and distribution measured on DECT with clinical presentation among patients with gout. Methods: We conducted a retrospective descriptive study of patients with gout who were referred by a rheumatologist for gout DECT scans between January 2008 and February 2018. At our institution, routine DECT scans for gout consist of four sets of images with limbs scanned in pairs: the hands/wrists, elbows, knees and ankles/feet. We obtained volumetric measurements for all four anatomical regions, and assessed the concordance with clinical presentation as retrieved from patient electronic health record. Results: A total of 182 patients were included in this study; 96 patients (80.2% male, age range: 27-90, mean age: 62) had urate deposits on DECT scans. Among urate-positive patients, the mean total volume of deposits was 2.45 cm 3 (hands/wrists: 0.17 cm 3, 7%; elbows: 0.62 cm 3, 25%; knees: 0.70 cm 3, 28%; ankles/feet: 0.96 cm 3, 39%). The average number of urate-positive joints was 2.5, higher than that of clinically symptomatic joints (1.9). Discordance between DECT results and clinical symptoms were seen more often in elbows (46 urate-positive vs. 22 symptomatic) and knees (68 vs. 43), compared with hands/wrists (31 vs. 30) and ankles/feet (90 vs. 87). Only in 25 (26.0%) patients, the distribution of symptomatic joints fully matched the distribution of urate deposits. In 6 patients (6.3%), there was no overlap between these two distribution patterns. Conclusion: On DECT scans, most urate deposits in gout patients occur in the ankles/feet, followed by knees, elbows, and hands/wrists. DECT scans can reveal urate deposit in asymptomatic joints, especially in elbows and knees. Assessing the concordance of urate distribution with clinical presentation in all limb joints in gout patients, our results can help understand the pathophysiology of urate deposition in gout, and guide the development of DECT protocols for the screening, assessment and follow-up management of gout patients. Reference: [1] Nicolaou S, Liang T, Murphy DT, Korzan JR, Ouellette H, Munk P. Dual-energy CT: a promising new technique for assessment of the musculoskeletal system. AJR Am J Roentgenol. 2012; 199:S78-86. Disclosure of Interests: Bo Gong: None declared, Mark Warwas: None declared, Michael O'Keeffe: None declared, Nicole Tsao: None declared, Mary De Vera: None declared, Kamran Shojania Shareholder of: Stock options in Augurex – biotech company., Grant/research support from: Doing a vasculitis study with BMS, Faisal Khosa: None declared, Savvas Nicolaou Grant/research support from: The Department of Radiology, Vancouver General Hospital has a Master Research Agreement with Siemens Healthcare, Forcheim, Germany (non-pharmaceutical company).